Brain MRI findings and their association with visual impairment in young adolescents born very preterm - Karimi Annette; Setänen Sirkku; Larsson Eva; Holmström Gerd; Kaul Ylva Fredriksson; Kochukhova Olga; Johansson Martin; Montgomery Cecilia; Hellström-Westas Lena; Wikström Johan (Springer, 2025)
Purpose
Very preterm birth increases risk for neonatal white matter injury, but there is limited data on to what extent this persists into adolescence and how this relates to ophthalmological outcomes. The aim of this study was to assess brain MRI findings in 12-year-old children born very preterm compared to controls and their association with concurrent ophthalmological outcomes.
Methods
We included 47 children born very preterm and 22 full-term controls (gestational age <32 and >37 weeks, respectively). Brain MRI findings were studied in association with concurrent ophthalmological outcomes at 12-year follow-up.
Results
Evans index (0.27 vs 0.25, p<0.001) and a proposed “posterior ventricle index” (0.47 vs 0.45, p=0.018) were increased in children born very preterm. Higher gestational age associated with larger corpus callosum area (β=10.7, 95%CI 0.59–20.8). Focal white matter lesions were observed in 15 (32%) of very preterm children and in 1 (5%) of full-term controls. Increased posterior ventricle index increased risk for visual acuity ≤1.0 (OR=1.07×1011, 95%CI=7.78–1.48×1021) and contrast sensitivity <0.5 (OR=2.6×1027, 95%CI=1.9×108–3.5×1046). Decreased peritrigonal white matter thickness associated with impaired visual acuity (β=0.04, 95%CI 0.002–0.07).
Conclusion
More white matter lesions and evidence of lower white matter volume were found in children born very preterm compared with full-term controls at 12-year follow-up. The association between larger posterior ventricle index and reduced visual acuity and contrast sensitivity suggests disturbances of the posterior visual pathway due to diffuse white matter lesions.